Does social businesses development affect bioenergy industry growth under the pathway of sustainable development? - Alsaleh, Mohammed; Abdulwakil, Muhammad Mansur; Abdul Rahim, Abdul Samad (Multidisciplinary Digital Publishing Institute, 2021)
The Treaty of European Union (EU) sets out the EU vision for sustainable development of Europe based on balanced economic growth and price stability, a highly competitive social market economy, aiming at full employment and social progress, and a high level of protection and improvement of the quality of the environment. This led us to ask whether or not social business development stimulates the development of the bioenergy sector in the EU28 countries. Given the increasing rates of energy insecurity, environmental pollution, poverty, and unemployment, countries are switching to alternative energy sources that might promote social business development, climate change, and environmental quality. In this scenario, the bioenergy industry has received the attention of scholars and policymakers alike. The role social business development can play in the growth of the bioenergy industry remains uncertain, therefore, further investigation is necessary. This study, therefore, explores the relationships between the bioenergy industry and social business development indicators related to zero emissions, zero poverty, and zero unemployment for EU28 region countries from 1990 to 2018. Empirical evidence is based on the use of a new economic model, dynamic panel co-integration simulations (Fully Modified Ordinary Least Square, Dynamic Ordinary Least Square, and Pooled Ordinary Least Square). The results reveal a negative relationship between EU28′s bioenergy industry growth and carbon dioxide emissions, vulnerable employment, and unemployment rate, suggesting that bioenergy industry growth helps reduce pollution and unemployment. Likewise, bioenergy industry growth increases food supply, economic growth, and female employment and might be the best alternative to fossil fuels. Necessary policy related to bioenergy industry growth can be formulated, especially in achieving the sustainable development goals for social businesses.